Advances in written text analysis - Coulthard, Malcolm (Routledge, 1994)
Advances in Written Text Analysis provides an overview of a wide range of exciting and compatible approaches to written text analysis. It includes both classic and specially commissioned papers, by distinguished authors, which share a common linguistic framework. The pieces contain a variety of focuses from the patterning of paragraphs, sections or whole texts to the organization of clauses, individual expressions and single words, as well as a variety of text-types.